Kaj1an Kebutuhan Inspektur Penerbangan Unit Kerja Kantor Otoritas Bandara Wilayah Ii Polonia-Medan - Siahaan, Juanda (Warta Penelitian Perhubungan, 2012)
The condition of Indonesia's aviation industry is currently experiencing significant grawth, but there is an imbalance between the growing number of passengers, the number of aircraft and the number of flight inspectors assigned check aircraft airworthiness. Based on the results of data processing at Airport Authority Office Region II is located in Medan Polonia-consist of the Prauince of Aceh, North Sumatra, Riau and Riau Islands. Today, for region II that the number of flight inspectors available are 44 people, while a necessary requirement is estimated as many as 85 people. TNhile the flight inspectors needs of each group of inspectors in the field of air transport aviation, airports, air navigation, aircraft airworthiness and operations and flight safety, aviation inspectors, flight inspectors needs compared to the standard does not meet the minimum requirements specified ratio is still one flight inspector versus 4 -5 planes, which means that future flight inspectors need more so would be good to support airline service performance. The method is done using qualitativedescriptive analysis method to aviation inspectors. To obtain the results of such studies necessary steps to meet the inspector attempts air transport, airports, aviation security, air navigation and aircraft airworthiness and operations assuming the Office of Airports Authority have at least 1 person inspector level 3 for each type of expertise and 4 flight inspector level 2 and have as many as 3 people inspector level 1 for each work area.Keywords: The Needs of Flight Inspectors, Airport Authority, Level Standard Kondisi industri penerbangan di Indonesia saat ini mengalami pertumbuhan yang sangat signifikan namun terjadi ketidakseimbangan antara pertumbuhan jumlah penumpang dan jumlah pesawat serta jumlah inspektur penerbangan yang bertugas memeriksa kelaikan pesawat. Berdasarkan hasil pengolahan data pada Kantor Otoritas Bandar Udara Wilayah II yang bertempat di Polonia-Medan terdiri dari Propinsi Nanggroe Aceh Darussalam, Sumatera Utara, Riau dan Kepulauan Riau. Untuk wilayah II bahwa jumlah inspektur penerbangan saat ini yang tersedia baru sebanyak 44 orang, sedangkan kebutuhan yang diperlukan diperkirakan sebanyak 85 orang. Sedangkan kebutuhan inspektur penerbangan dari masing-masing kelompok inspektur penerbangan di bidang angkutan udara, bandar udara, navigasi penerbangan, kelaikudaraan dan pengoperasian pesawat udara serta keamanan penerbangan, jumlah inspektur penerbangan belum sesuai dibandingkan dengan standar kebutuhan rmmmal yang ditetapkan rasionya masih 1 inspektur penerbangan berbanding 4-5 pesawat, yang artinya kedepan semakin banyak inspektur penerbangan dibutuhkan sehingga akan lebih baik dalam mendukung kinerja pelayanan penerbangan. Metode yang dilakukan dengan menggunakan metode analisis deskriptif kualitatif terhadap inspektur penerbangan. Untuk memperoleh hasil kajian tersebut diperlukan langkah-langkah upaya untuk memenuhi inspektur angkutan udara, bandar udara, keamanan penerbangan, navigasi penerbangan dan kelaikudaraan dan pengoperasian pesawat udara dengan asumsi Kantor Otoritas Bandar Udara sekurang-kurangnya memiliki 1 orang inspektur level 3 untuk tiap jenis bidang keahliannya dan 4 orang inspektur penerbangan level 2 serta memiliki sebanyak 3 orang inspektur level 1 untuk tiap wilayah kerja. Kata kunci: Kebutuhan Inspektur penerbangan, Otoritas Bandara, Standar Level